PERLAKUAN DISKRIMINASI TERHADAP MAHASISWA PAPUA DI KOTA STUDI YOGYAKARTA - Kapisa, Imfakwak (Commsphere: Jurnal Ilmu Komunikasi, 2023)
Discrimination is still often found in society due to differences in race, gender and religion. Discrimination itself is an action that is a phenomenon that violates human rights law. In general, discrimination occurs because the majority group corners minority groups because groups that have power can act according to their wishes on different minority groups. Especially acts of discrimination against Papuans, acts of discrimination make the majority of Papuans who have migrated feel depressed or even alienated because of the discrimination. This is the background for researchers to look at the negative stigma towards Papuans and in dealing with acts of discrimination that occur in Yogyakarta. Keywords: Discrimination, Race, Culture, Religion, Multiculturalism.